2016
DOI: 10.1016/j.heares.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Volumes of cochlear nucleus regions in rodents

Abstract: The cochlear nucleus receives all the coded information about sound from the cochlea and is the source of auditory information for the rest of the central auditory system. As such, it is a critical auditory nucleus. The sizes of the cochlear nucleus as a whole and its three major subdivisions – anteroventral cochlear nucleus (AVCN), posteroventral cochlear nucleus (PVCN), and dorsal cochlear nucleus (DCN) - have been measured in a large number of mammals, but measurements of its subregions at a more detailed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 106 publications
(193 reference statements)
1
5
0
Order By: Relevance
“…(mountain beaver) of the total cochlear nucleus volume (cat: 35%; Osen, 1969). Godfrey et al (2016) interpreted these features of the DCN as possible adaptations facilitating the integration of somatosensory and auditory stimuli in the underground habitat which is in line with the interpretation of the dorsal cochlear nucleus in mammals, generally (see also Malmierca, 2015). The granule cells of the DCN receive direct input from many sources including the trigeminal somatosensory system and this information is likely processed in the molecular layer (Young & Davis, 2002).…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…(mountain beaver) of the total cochlear nucleus volume (cat: 35%; Osen, 1969). Godfrey et al (2016) interpreted these features of the DCN as possible adaptations facilitating the integration of somatosensory and auditory stimuli in the underground habitat which is in line with the interpretation of the dorsal cochlear nucleus in mammals, generally (see also Malmierca, 2015). The granule cells of the DCN receive direct input from many sources including the trigeminal somatosensory system and this information is likely processed in the molecular layer (Young & Davis, 2002).…”
Section: Resultssupporting
confidence: 56%
“…While being less laminated than in the rat, the DCN of the Ansell's mole‐rat is characterized by a thickened molecular layer (DCMo, plate 940, Figure ) and an enlarged granular layer (GrC, plate 920). A prominent DCN has also been reported for the tunnel‐dwelling mountain beaver ( Aplodontia rufa ) and the subterranean pocket gopher (Godfrey et al, ). In these species, the DCN amounts to more than 60% (pocket gopher) or almost 90% (mountain beaver) of the total cochlear nucleus volume (cat: 35%; Osen, ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…We also used data from Carter et al (2004) to estimate the volume of the bat CN. Results showed that the bat CN exhibits substantial hypertrophy (total volume 1.15 mm 3 ), compared to the total volume of the mouse CN at 0.6 mm 3 (Muniak et al 2013, Godfrey et al 2016). Surprisingly, a larger percent area of the mouse CN compared to the bat’s expressed Cx36.…”
Section: Discussionmentioning
confidence: 92%